Protein turnover, requirements, and how to use it according to the clinical situation in patients with parenteral nutrition - Adriana Flores-López; Martha Guevara-Cruz; Armando R. Tovar; Nimbe Torres; Aurora E. Serralde-Zúñiga (Revista Médica del Hospital General de México, 2025)
Of the three primary macronutrients, protein requirements vary the most because of different factors that make them change the requirements when we calculate them. The utilization and degradation of amino acids (AAs) may vary according to the pathology or condition of the patient. A better understanding of the basis of protein turnover and its responses to different situations will help to have better prescriptions. In recent years, there has been considerable information about the use of protein and specific AAs, such as branched-chain AAs and glutamine in the treatment of different conditions or pathologies, such as in elderly individuals; in those in intensive care units; and individuals with cancer, sepsis, or kidney or liver diseases. Thus, the present work aims to recapitulate and define the appropriate protein requirements in these different conditions and how to administrate when prescribed parenteral nutrition.